Higher-Order Thalamic Encoding of Somatosensory Patterns and Bilateral Events - Castejon, Carlos; Martin-Cortecero, Jesus; Nuñez, Angel (Frontiers in Neural Circuits, 2021)
The function of the higher-order sensory thalamus remains unclear. Here, the posterior medial (POm) nucleus of the thalamus was examined by in vivo extracellular recordings in anesthetized rats across a variety of contralateral, ipsilateral and bilateral whisker sensory patterns. We found that POm was highly sensitive to multiwhisker stimuli involving diverse spatiotemporal interac¬tions. Accurate increases in POm activity were produced during the overlapping time between spatial signals reflecting changes in the spatiotemporal structure of sensory patterns. In addition, our results showed for first time that POm was also able to respond to tactile stimulation of ipsilateral whiskers. This finding challenges the notion that the somatosensory thalamus only computes unilateral stimuli. We found that POm also integrates signals from both whisker pads and described how this integration is generated. Our results showed that ipsilateral activity reached one POm indirectly from the other POm and demonstrated a transmission of sensory activity between both nuclei through a functional POm-POm loop formed by thalamocortical, interhemispheric and corticothalamic projections. The implication of different cortical areas was investigated revealing that S1 plays a central role in this POm-POm loop. Accordingly, the subcortical and cortical inputs allow POm but not the ventral posteromedial thalamic nucleus (VPM) to have sensory information from both sides of the body. This finding is in agreement with the higher-order nature of POm and can be considered to functionally differentiate and classify these thalamic nuclei. A possible functional role of these higher-order thalamic patterns of integrated activity in brain function is discussed.